Comparative evaluation of tumor targeting using the anti-HER2 ADAPT scaffold protein labeled at the C-terminus with indium-111 or technetium-99m. Issue 1 (December 2017) - Garousi, Javad; Lindbo, Sarah; Mitran, Bogdan; Buijs, Jos; Vorobyeva, Anzhelika; Orlova, Anna; Tolmachev, Vladimir; Hober, Sophia
Abstract ABD-Derived Affinity Proteins (ADAPTs) is a novel class of engineered scaffold proteins derived from an albumin-binding domain of protein G. The use of ADAPT6 derivatives as targeting moiety have provided excellent preclinical radionuclide imaging of human epidermal growth factor 2 (HER2) tumor xenografts. Previous studies have demonstrated that selection of nuclide and chelator for its conjugation has an appreciable effect on imaging properties of scaffold proteins. In this study we performed a comparative evaluation of the anti-HER2 ADAPT having an aspartate-glutamate-alanine-valine-aspartate-alanine-asparagine-serine (DEAVDANS) N-terminal sequence and labeled at C-terminus with99m Tc using a cysteine-containing peptide based chelator, glycine-serine-serine-cysteine (GSSC), and a similar variant labeled with111 In using a maleimido derivative of 1, 4, 7, 10-tetraazacyclododecane-1, 4, 7, 10-tetraacetic acid (DOTA) chelator. Both99m Tc-DEAVDANS-ADAPT6-GSSC and111 In-DEAVDANS-ADAPT6-GSSC-DOTA accumulated specifically in HER2-expressing SKOV3 xenografts. The tumor uptake of both variants did not differ significantly and average values were in the range of 19–21%ID/g. However, there was an appreciable variation in uptake of conjugates in normal tissues that resulted in a notable difference in the tumor-to-organ ratios. The111 In-DOTA label provided 2–6 fold higher tumor-to-organ ratios than99m Tc-GSSC and is therefore the preferable label for ADAPTs.